(untitled) (Current Horticulture, 2024)
The study was undertaken to know the attitude of farmers towards guava (Psidium guajava L.) cultivation in Sawai Madhopur district of Rajasthan (India) during 2013. Data were solicited from randomly selected 180 guava growers in Sawai Madhopur district. A five-point Likert rating scale was applied. The results showed that most of the farmers had positive attitude towards guava growing due to more income. They perceived that cultivation of guava can boost their economy (92.22%) because of its cultivation is easier to unskilled farmers (54.44%). Farmers perceives that cultivation of guava is labour intensive enterprise (84.45%)and they had positive attitude for that lack of supportive Government policy is a big hindrance in guava plants cultivation (58.88%) and subsidy is better option for government to promote guava cultivation (91.66%). Since majority of guava cultivators in SawaiMadhopur belongs to tribal community, therefore assistance from government side is better option for economic empowerment of farmers as well as high yield of guava. Farmers were also in agreement with that motivation agencies in the area play a vital role in the promotion of guava crops (57.22%).The farmers, if provided adequate credit facility, can be attracted towards cultivation of guava (87.78%).